Keterbasahan Kayu Jati Cepat Tumbuh Termodifikasi Kimia dan Panas: Wettability of Chemically and Thermally Modified of Fast-Growing Teak Wood - Hanifah, Nisrina Putri; Wahyuningtyas, Irma; Kutana, Agung Nugrawan; Dirna, Fitria Cita (Forestry Faculty of Hasanuddin University, 2025)
Fast-growing species are chemically and thermally modified to improve quality. These changes affect wood’s chemical composition and surface characteristics. This study aims to analyze the durability of fast-growing teak wood that has been chemically and thermally modified. Chemical modification was carried out by impregnation using citric acid and polyethylene glycol (PEG) 400, while heat modification carried out at 150 °C. The wettability of wood was tested by measuring the contact angle with six types of liquid, aquades, toluene, glycerin, methanol, alkyd, and acrylic paint. The results showed that chemical modification treatment significantly improved the wettability of wood compared to control and heat treatment. Wood treated with citric acid and PEG 400 exhibits a lower contact angle, indicating increased liquid absorbency. Conversely, heat treatment increased the contact angle value making the wood more hydrophobic. Alkyd showed better wettability than acrylic paints, possibly due to their lower viscosity values. This suggests that chemical modification more effectively improves wood coating adhesion.